Avaliação de 'Wetlands' construídos no pós-tratamento de efluente de lagoa de maturação - Ormonde, Vanusa Soares da Silva (2012)
This study aimed to evaluate 5 units in a pilot scale of constructed wetlands by horizontal subsurface flow, treating the effluent from a maturation pond operating at real scale in the city of Cuiabá-MT. The evaluation period lasted eight months totaling sixteen campaigns. The experimental system consisted of five units dug in the ground and built of brick, with dimensions of 5m long, 2m wide and 0.60 m deep each. System performance was compared in terms of removal of BOD, COD, total phosphorus, TSS, and turbidity. Considering as filler sand with a percentage of fines (silt and clay) equal to 13.84%, and four beds planted with Zea maiz, Canna indica, Canna x generallis and Colocassia esculenta respectively, and a control plot (without vegetation). Average removals were found between 44.34 and 50.92% for BOD and between 56.26 and 63.24% for COD in wetlands systems. For other variables such as SST turbidity and phosphorus removal was achieved maximum 83.88%, 95.4% and 59.79 respectively. Concerning the adaptability of plants, species Canna indica and Canna x generalis obtained better results, however Colocassia esculenta showed yellowing of leaves after three months of operation.